BILANGAN RADIO PADA GRAF SIKEL DENGAN DAN GRAF SIKEL TENGAH - Meivita Nur Arifiani; R. Heru Tjahyana (Jurnal Matematika, 2014)
ABSTRACT.Let   be a simple connected graph and  denote the distance between any two vertices in . The maximum distance between any pair of vertices is called the diameter denoted by . A radio labeling for  is an injectif function  such that for any vertices  dan  it is satisfied that . The span of an radio labeling  is max  . The minimum span of a radio labeling of  is called radio number denoted by . In this Thesis we study radio number of  cycle with  and  graph of cycle .